Faithful to science : the role of science in religion - Steane, Andrew M. (United Kingdom.: : Oxford University Press, 2014)
Science and religious faith are two of the most important and influential forces in human life, yet there is widespread confusion about how, or indeed whether, they link together. This book describes this combination from the perspective of one who finds that they link together productively and creatively.
Part I. Science and nature. Faith and engagement -- Science and faith -- The nature of the physical world -- Autobiographical sketch -- Keeping science -- The book of marvels -- Half way -- Part II. Origins. The argument from design -- Genesis -- Human origins -- Comparing notes -- Final comments -- Appendix: Two legends.
Includes bibliographical references and index.
Keywords: Religion and science